Sustaining wheat (Triticum aestivum) revolution-retrospect and prospect - NAGARAJAN, N; SHARMA, GHANSHYAM (The Indian Journal of Agricultural Sciences, 2013)
During 1961-71 there was a speedy increase in productivity in all the major wheat (Triticum aestivum L.emend. Fiori & Paol.)-growing states of the Indo-Gangetic plains. However, the next 10 years had a slow growth rate. This slowing down of growth raised many doubts on the sustainability of the system, on the very success of the Green Revolution itself. and was even termed as the Green Revolution fatigue. The subsequent decade witnessed that there is a possibility of further increase in food production. It also indicates that there is a large amount of unharvested yield in Uttar Pradesh, Bihar, Madhya Pradesh and Gujarat where average productivity levels at best equal the national average. Nearly 14 million ha come under this category and even if the average yield is increased by I tonne that will stceply increase the total production.Â Since there is no scope for area expansion, additional production has to come by increasing the per hectare productivity. This implies that the current all-India average wheat yield of 2700 kg/ha has to be increased to 4200 kg/ha in the next 25 years. During 1995-96. India exported wheat worth Rs 900 million and a major amount was of bread wheat. From export point of view durum wheat (T.durum Desf.) appears to be better placed because less number of varieties with wider adaptability are available in the country. Also, they meet most of the international quality standards. There is a great potential to double or triple the quantum of export. There are also futuristic opportunities, since new technological innovations are likely to occur. The development of very high-yielding varieties by converging new genes from different sources; development of hybrid wheat varieties and the potential of new plant types through biotechnology are some of thc exciting opportunities which can push the yield to 9 tonnes/ha. In such a situation, wheat production from the North-western plains zone will increase substantially and through several front-line demonstrations, it has been shown that this fertile tract can easily yield 4.5 tonnes/ha, ie nearly 1.5 tonnes/ha more than the current levels.